EDUCATION ON GADGET INTENSITY AND YOUTH EMPOWERMENT IN PREVENTING CARPAL TUNNEL SYNDROME WITH EXERCISE - Isna Andriani; Maoli Zartika; Muhammad Akhir Purnomo (LPPM Universitas Abdurrab, 2026)
Excessive smartphone use among adolescents has been linked to increased risk of musculoskeletal complaints, including early symptoms of Carpal Tunnel Syndrome (CTS) due to repetitive wrist and finger movements that affect the median nerve. Lack of awareness regarding proper gadget use and preventive exercises may worsen the risk over time. Therefore, community education and youth empowerment were essential to promote healthier digital habits. This community service program aims to prevent median nerve–related problems by increasing knowledge, awareness, and self-efficacy among youth regarding safe smartphone use and simple exercises for CTS prevention. The community service program was conducted at SMA PK Muhammadiyah Kottabarat, with a total of 75 participants. The intervention was delivered through educational sessions and empowerment activities, utilizing visual and interactive media including PowerPoint presentations, banners, and informational flyers. Participants received education on gadget intensity, ergonomics, early CTS symptoms, and preventive wrist-hand exercises. Youth participants were also be involved as peer ambassadors to reinforce healthy behaviors within their community. The program improved participants’ understanding of safe smartphone practices, increase awareness of CTS prevention strategies, and enhance motivation to perform regular exercises. Youth empowerment activities were anticipated to support sustained behavioral change and broader community dissemination. “Smartphone Smart Use” education combined with youth empowerment provides an effective approach to preventing median nerve issues related to excessive gadget use. Through structured learning materials and active youth involvement, this program supports healthier digital habits and reduces the risk of Carpal Tunnel Syndrome among adolescents.